(untitled) (Revista LIDER, 2020)
This article analyzes the innovation capacities of a group of firms from the locality of Bahia Blanca. Using a Logit model, one concludes that the innovation of the firms is related to the ages of the owners, the employees´ skills, the contacts made with corporate unions and other variables.